“What Should I Do after All of This?": Behavioral Engagement in Writing Class with Teacher Feedback - Siti Mafulah; Maftuch Junaidy Mhirda; Wahyuningsih Usadiati; Sanwal Haider (JEELS (Journal of English Education and Linguistics Studies), 2025)
Teacher feedback is one of the alternative ways to help students improve their writing performance. Few studies have confirmed students’ deep exploration of how students engage behaviourally with teacher feedback. Therefore, this study aims to find out the behavioural engagement of the students after receiving feedback as well as what factors influenced it. Case study design was applied in this study through delivering questionnaires and interviews. The participants of this study were the third-year university students in Malang, Indonesia. The finding of this study highlights that high-proficiency students tend to ask the teacher when they do not understand the feedback, while moderate- and low-proficiency levels tend to ask their friends. In addition, factors that influenced students’ behavioural engagement are internal factors such as self-efficiency and self-awareness and external factors such as the teacher’s way of teaching and internet connection. It is suggested that teachers should know their student’s behavioural engagement to gain learning outcomes.